2004
DOI: 10.1016/j.jhsb.2003.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Epidemiological Variation of Anomalous Muscles at Guyon’s Canal

Abstract: Ultrasound was performed in 116 wrists of asymptomatic volunteers to determine the prevalence and morphology of anomalous muscles in Guyon's canal in the normal population. The size of the muscle was correlated with sex, hand-dominance and occupation. Anomalous muscles were identified in 47% of volunteers and 35% of wrists (male prevalence (50%); female prevalence (21%)). All were variants of abductor digiti minimi. Bilateral muscles were present in 50% of index cases in both sexes. Mean muscle thickness was 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 12 publications
1
53
0
4
Order By: Relevance
“…The most frequent muscle variants documented in the literature on the hypothenar region relate to the abductor digiti minimi (Harvie et al, 2004), which has been reported to have a very variable origin and to insert into the proximal phalanx or into the extensor aponeurosis (Putz and Pabst, 1999;Tillman and Töndury, 1987;Kanaya et al, 2002;Murata et al, 2004). None of the many and varied case reports, however, matches the single constellation we saw in this study; the variant was found in both hands, was approximately as thick as the flexor digiti minimi and was innervated from a branch of the main trunk of the ulnar nerve.…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent muscle variants documented in the literature on the hypothenar region relate to the abductor digiti minimi (Harvie et al, 2004), which has been reported to have a very variable origin and to insert into the proximal phalanx or into the extensor aponeurosis (Putz and Pabst, 1999;Tillman and Töndury, 1987;Kanaya et al, 2002;Murata et al, 2004). None of the many and varied case reports, however, matches the single constellation we saw in this study; the variant was found in both hands, was approximately as thick as the flexor digiti minimi and was innervated from a branch of the main trunk of the ulnar nerve.…”
Section: Discussionmentioning
confidence: 99%
“…These variations are reported as anomalous palmarislongus, [15,16] flexor digiti minimi brevis [17,18] or abductor digiti minimi muscle, [14,15,17,[19][20][21][22][23] a variantabductor-flexor muscle of the little finger, [24] accessory flexor profundus [25] or flexor carpi ulnaris [15,26] muscles coursing through the canal. [27,28] In this study, an accessory abductor digiti minimi muscle was observed as a possible cause of compression in Guyon's canal, creating a fibrous arch over the nerve.…”
Section: Discussionmentioning
confidence: 73%
“…Anatomical reports describe that, muscle variations at the distal forearm are frequent, and are mostly reported by radiologists during MRI or ultrasound imaging studies (Zeiss & Jakab, 1995;Zeiss & Guilliam-Haidet;Ruocco et al;Schuurman & van Gils 2000;Yildiz et al;Bencteux et al, 2001;Harvie et al). Accessory muscles located at the palmar aspect of the distal forearm are highly variable in their morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Nerve compression by anomalous muscles located at the wrist and distal forearm is an infrequent condition, few reports exist in literature (Zeiss & Guilliam-Haidet, 1996;Ruocco et al, 1998;Harvie et al, 2004). Accessory muscles may compress underlying structures in the carpal tunnel region or ulnar canal, causing pain and paresthesias (Morrison, 1916;Ryu & Watson, 1987;Sañudo et al, 1993;Server et al, 1995;Sanchez Lorenzo et al, 1996;Depuydt et al, 1998;Santoro et al, 2000;Schuurman & van Gils, 2000;Soldado-Carrera et al, 2000;Bozkurt et al, 2005;Jones, 2006, Acikel et al, 2007Ogun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%